Neuroeducación infantil temprana: integrando la neurociencia al proceso de aprendizaje en la primera infancia: una revisión sistemática - Llatance Ruiz, Ingrid del Pilar (2024)
The objective of the study was to know the importance of neuroscience in Latin America in the teaching-learning process of the pre-school stage.  The study was a systematic narrative review in the databases Scielo, Redalyc, Dialnet, REDIB and the Latin American Journal of Early Childhood Education (RELAdEI) under the search criteria of the words: neuroscience, learning process, neuroeducation from 2018 to 2023. The review mainly included articles published between 2019 and 2023 (94%), reflecting a very up-to-date approach to children's neuroeducation. The year with the most contributions is 2019 (26%), closely followed by 2021 (24%). The set allows us to analyze the recent state of the art on the integration of neuroscience into early teaching-learning in Latin America. The growing research interest in this emerging synthesis of disciplines to enhance pedagogy is evident. The progressive integration of neuroscience into early childhood pedagogical practices was concluded. The analysis of recent scientific production from 2019 confirms the dizzying increase in research on the application of neurobiological knowledge to transform and enhance early teaching-learning processes.